Eksistensi Desa Dawan Berdasarkan Rekaman Prasasti Prasi A - I Wayan Srijaya; Kadek Dedy Prawirajaya R. (AMERTA, 2024)
Abstract. The Existence of Dawan Village Based on Records of Prasi Inscriptions A. Inscriptions are one of the sources with very good authenticity value. This is because the inscriptions were issued directly on the orders of the king or ruler. Inscriptions, as written sources  revealing various aspects of past life, are written using different scripts and languages. Some use the Prenagari script and Sanskrit, Old Javanese script and the Old Javanese, Old Balinese script and the Old Balinese, and so on. In this study, the inscription used to reveal the existence of Dawan Village is the Prasi A inscription issued in the Çaka year of 1070 (1148 AD) by King Sri Maharaja Jayasakti. This king was one of the rulers of the ancient Balinese kingdom who, during his reign, issued many inscriptions. This Prasi A inscription was issued by the king at the request of karaman i besan whose agricultural land was taken over by karaman i dahwan/dawan. karaman i besan request was granted by the king so this inscription was issued. Since then, karaman i besan has received the king’s grace to strengthen the previous king’s grace. Apart from that, the inscription also includes a sapatha, or curse, for anyone who dares to violate this gift so that they will be punished, along with an appeal to the gods. Keywords: Dawan Village, Sri Maharaja Jayasakti, 9-14th Century   Abstrak. Prasasti merupakan salah satu sumber yang memiliki nilai autentitas sangat baik. Hal ini disebabkan karena prasasti dikeluarkan langsung atas perintah raja atau penguasa. Prasasti sebagai sumber tertulis dalam mengungkap berbagai aspek kehidupan masa lalu, ditulis dengan menggunakan aksara dan bahasa yang berbeda-beda. Ada yang memakai aksara Prenagari dan bahasa Sansekerta, aksara Jawa Kuno dan bahasa Jawa Kuno, aksara Bali Kuno dan bahasa Bali Kuno, dan lain sebagainya. Dalam penelitian ini, prasasti yang digunakan untuk mengungkap eksistensi Desa Dawan adalah Prasasti Prasi A yang dikeluarkan tahun  1070 S (1148 M) oleh raja Sri Maharaja Jayasakti. Raja ini merupakan salah satu penguasa kerajaan Bali Kuno yang selama memerintah mengeluarkan banyak prasasti. Prasasti Prasi A ini, dikeluarkan raja atas permohonan karaman i besan yang lahan pertaniannya diambil alih oleh karaman i dahwan/dawan. Permohonan untuk mengatasi pengambilan lahan milik karaman i besan dikabulkan oleh raja sehingga dikeluarkanlah prasasti ini. Sejak saat itu karaman i besan mendapat anugrah raja untuk menguatkan kembali anugrah raja sebelumnya. Selain itu, dalam prasasti disertakan pula sapatha atau kutukan kepada siapa saja yang berani melanggar anugerah ini agar mendapat sanksi disertai pula seruan kepada dewa-dewa. Kata kunci: Desa Dawan, Sri Maharaja Jayasakti, Abad ke-9-14